Potential application of pure silica optical flat fibers for radiation therapy dosimetry. (January 2015) - Alawiah, A.; Bauk, S.; Abdul-Rashid, H.A.; Gieszczyk, W.; Hashim, S.; Mahdiraji, G.A.; Tamchek, N.; Bradley, D.A.
Abstract: Pure silica optical flat fibers (FF) have been proposed as the basis for a novel radiation sensor by the measurement of the thermoluminescence (TL) produced. In this paper the TL performance of the FFs were studied. Using a linear accelerator (LINAC) delivering doses in the range 0.2–10.0 Gy, the TL dosimetric glow curves of the FFs were studied with respect to 6 MeV electron and 6 MV photon beams. When exposed to 6 MeV electron irradiation, the pure silica FFs displayed a supralinear response starting from 2 Gy up to 10.0 Gy. While for 6 MV photon irradiation, the FFs shows linear characteristic ( f ( D ) = 1 ) nearly up to 2 Gy. The TL intensity ( I m ) of the main peak of FFs is 1.5 times higher for 6 MeV electron beams than for 6 MV photon beams. The maximum peak temperature ( T m ) it is not affected by the type of irradiation used at the same dose while the maximum TL intensity ( I m ) was found to be dependent on the type of radiation used. Overall results indicate that the pure silica FFs can be used as radiation sensors in the high-dose therapy dosimetry. Highlights: TL intensity ( I m ) is 1.5 times higher for 6 MeV electron than 6 MV photons beams. The T m is not affected by the type of irradiation used at the constant dose. The FFs displayed a supralinear response from 2 Gy up to 10.0 Gy. The sensitivity of FFs to electrons is consistently higher than photons.